MISSIO DEI DALAM PERJANJIAN LAMA: ALLAH YANG AKTIF DALAM SEJARAH UMAT MANUSIA - Kawuhuang, Stefhany; Matheos, Frigita; Jacobus, Theresia Verolis; Panawar, Jesica; Lengkong, Nadia Melani (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2025)
This article discusses the concept of Missio Dei in the Old Testament by emphasizing that God is the main Subject of the mission who works actively in human history to realize His plan of salvation. Through a descriptive qualitative approach and literature study, this article shows that God's work in creation, the covenant with Abraham, the liberation of Israel, the prophecies of the prophets, and the Messianic hope are integral parts of Missio Dei. God does not only act in the context of the nation of Israel, but directs His mission to all nations and creation. God's mission in the Old Testament includes spiritual, social, and ethical aspects, such as justice, restoration, and liberation from oppression. This article also highlights the theological and missiological implications for the church today, that the church is called to continue God's mission by being contextual, relevant to the digital age, and present in cross-cultural dialogue and service as a form of participation in God's work of salvation.